eCM 2019
DOI: 10.22203/ecm.v038a04
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and in vitro and in vivo evaluation of supercritical-CO2-foamed β-TCP/PLCL composites for bone applications

Abstract: Most synthetic bone grafts are either hard and brittle ceramics or paste-like materials that differ in applicability from the gold standard autologous bone graft, which restricts their widespread use. Therefore, the aim of the study was to develop an elastic, highly porous and biodegradable β-tricalciumphosphate/poly(Llactide-co-ε-caprolactone) (β-TCP/PLCL) composite for bone applications using supercritical CO 2 foaming. Ability to support osteogenic differentiation was tested in human adipose stem cell (hASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Pitkänen et al [ 25 ] worked out the contradicting results on the osteoinductive properties of β-TCP and were speculating that they might vary according to the surface properties of the material [ 26 , 27 ]. The brittle and hard calcium phosphates are very difficult to shape and implant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pitkänen et al [ 25 ] worked out the contradicting results on the osteoinductive properties of β-TCP and were speculating that they might vary according to the surface properties of the material [ 26 , 27 ]. The brittle and hard calcium phosphates are very difficult to shape and implant.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups reported that bone implants with a highly porous structure enhance immigration of (stem) cells [ 33 ] and the cellular induced deposition of minerals, a prerequisite of bone regeneration [ 25 ] and bone marrow niche homeostasis [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The monomer ratio of ε-caprolactone and lactide can be changed to alter the mechanical properties of the PCLLA copolymer, which can confer rubber-like elasticity. 22 In this study, a threearm macromolecule of PCLLA chains was polymerized via the copolymerization of ε-caprolactone and lactide. The process was initiated by hydroxyl groups of TMP.…”
Section: Discussionmentioning
confidence: 99%
“…24 Pihlman et al reported β-tricalcium phosphate and PLCL by supercritical CO 2 processing, which was further applied in a rabbit calvarial defect and showed good biocompatibility with improved angiogenesis and osteogenesis effect. 25,26 Akkouch et al designed a Coll/HA/PLCL scaffold, and the osteoblasts cultured on the composite displayed positive cell behavior and superior osteogenic phenotype. 27…”
Section: Introductionmentioning
confidence: 99%
“…24 Pihlman et al reported b-tricalcium phosphate and PLCL by supercritical CO 2 processing, which was further applied in a rabbit calvarial defect and showed good biocompatibility with improved angiogenesis and osteogenesis a State Key Laboratory of Oral Diseases, National Clinical Research Center for Oral effect. 25,26 Akkouch et al designed a Coll/HA/PLCL scaffold, and the osteoblasts cultured on the composite displayed positive cell behavior and superior osteogenic phenotype. 27 Although PLCL showed great potential as a degradable carrier for bone grafts, it was challenging to achieve high content and homogenous dispersion of inorganic particles in the polymer during manufacturing.…”
Section: Introductionmentioning
confidence: 99%